A new practical approach to evaluate near wellbore formation damage parameter based on well test analysis for gas reservoir - Kome, M.; Amro, M.; Hossain, Mofazzal (SPE, 2012)
Prediction of degree of near-wellbore damaged caused during drilling and completion is extremely difficult and challenging in any reservoir development program. It plays a vital role on decision making, specifically when the decision has to be made based on inflow performance relationship (IPR) analysis. Skin factor used for most of the IPR models are either calculated from analytical models depending on the near wellbore conditions (e.g. open hole, perforated, gravel packing etc.); or predicted based on expensive well test data. While accuracy of the predicted results depends on the accuracy of input parameters available to feed into model, nevertheless this approach can generate range of uncertainties with misleading predicted results that significant effect on decision making. This paper presents a simplified practical method of estimating the extent of damage and amount of skin in a reservoir. Correlations for the permeability in the damage zone have been developed as a function of the average reservoir permeability in the drainage area of reservoirs for steady, stabilized or transient flow conditions. The model uses well deliverability test data to predict average permeability in the drainage zone. The model has been applied to different cases using representative field test data for high and low permeable reservoirs. It has been demonstrated that the proposed model exhibits very good approximation of damage components affecting reservoirs. From this analysis, it could also be concluded that by using data from unsteady flow deliverability tests, it is possible to get a good estimation of the damage skin in a reservoir and its extent. This is valid as long as the damage does not exceed the transient drainage radius. Exceeding the transient drainage radius will imply deriving very large skin values from the test, and this is rare in most cases.